Adherence to a healthy lifestyle of the Russian population depending on the socio-demographics - S. A. Shalnova; S. A. Maksimov; Yu. A. Balanova; S. E. Evstifeeva; A. E. Imaeva; А. V. Kapustina; N. S. Karamnova; G. A. Muromtseva; I. A. Viktorova; N. N. Prishchepa; A. N. Redko; S. S. Yakushin; et al. (Кардиоваскулярная терапия и профилактика)
Aim. To assess the relationship of the population’s adherence to a healthy lifestyle (HLS) with socio-demographics and to carry out a comparative analysis of adherence according to ESSE-RF-1 and ESSE-RF-2 studies.Material and methods. This study was conducted as part of a multicenter epidemiological study ESSE-RF-2 in 4 regions of Russia (n=5897). The following components of HLS were considered: non-smoking, adequate consumption of fruits and vegetables, salt intake, regular physical activity, and low alcohol consumption. According to the combination of components, “high”, “adequate” and “low” adherence to HLS were distinguished. The socio-demographics included gender, age, region, residence (urban/rural), marital status, educational status, income. To compare the results with other studies, the data obtained were standardized according to the 1976 European Standard Population age structure.Results. Initial data on adherence to healthy lifestyle were as follows: high adherence — 21,9%, adequate — 34,5%, low — 43,6%. We observed the following prevalence of low adherence components: excessive salt intake (50,5%), insufficient consumption of fruits and vegetables (37,5%), smoking (22,7%), low physical activity (19,6%), excessive alcohol consumption (4,9%). High adherence to HLS was associated with female gender, older age, urban residence, high educational status, absence of family. In addition, the combined effects of socio-demographics on adherence to HLS were revealed. In particular, we analyzed the effect of high educational status with other characteristics (gender, age, residence), which acted both as a protective and negative factor. A comparative analysis of ESSE-RF-1 and ESSE-RF-2 data showed significant differences in the prevalence of adherence to HLS, which may be due to both methodological differences of studies and a true change in adherence to HLS.Conclusion. High adherence to HLS is detected only in every fifth adult of the studied regions. Low adherence to HLS is associated with a number of socio-demographic characteristics of the population and is specified mainly by the high prevalence of unhealthy diet and, to a lesser extent, low physical activity and smoking.